Pengaruh Rasio-Rasio Keuangan Terhadap Financial Distres Pada Perusahaan Sektor Perdagangan, Jasa, Dan Investasi - Abdul Hadi (Jurnal Ilmu Manajemen, 2022)
Financial distress is a decrease in financial conditions before bankruptcy. These financial difficulties do not happen suddenly. However, one indication that causes financial distress is a continuous decline in company profits. This study aims to examine financial ratios' effects on financial distress. Independent variables of financial ratios used in this research are current ratio, return on assets, debt to equity ratio, debt to assets ratio, and total assets turnover. The used in this study is from 2018 to 2020. The population used in this study includes companies engaged in trade, services, and investment. The sample used is purposive sampling to produce as many as 39 companies as samples. The analysis used in this study is logistic regression analysis. The results showed that the current ratio also returns on assets had a significant impact on financial distress. In the meantime, the independent variables debt to equity ratio, debt to assets ratio, and total assets turnovers do not affect financial distress. Trade, service, and investment sector companies can increase sales to maximise profits and pay off the short-term obligations.